COVID-19 Effect on Access to Maternal Health Services in Kenya - Oluoch-Aridi, Jackline; Chelagat, Tecla; Nyikuri, Mary M.; Onyango, Joseph; Guzman, Danice; Makanga, Cindy; Miller-Graff, Laura; Dowd, Robert (Frontiers in Global Women's Health, 2020)
Introduction. Maternal mortality continues to be one of the biggest challenges of the health system in Kenya. Informal settlements in Kenya have been known to have higher rates of maternal mortality and are also known to receive maternity services of varied quality. Data assessing progress on key maternal health indicators within informal settlements are also often scarce. The COVID-19 pandemic hit Kenya in March this year and so far, the impact of the COVID-19 pandemic on access to maternal health has not been established. This study aims to add to the body of knowledge by investigating the effects of the COVID-19 pandemic and mitigation strategies on access to health care services in informal settlements. Methods. Qualitative methods using in-depth interviews were used to assess women’s experiences of maternity care during the COVID-19 era and the impact of proposed mitigation strategies such as the lockdown and the curfew. Other aspects of the maternity experience such as women’s knowledge of COVID-19, their perceived risk of infection, access to health facilities, perceived quality of care were assessed. Challenges that women facing as a result of the lockdown and curfew with respect to maternal health access and quality were also assessed. Results. Our findings illustrate that there was a high awareness of the symptoms and preventative measures for COVID-19 amongst women in informal settlements. Our findings also show that women’s perception of risk to themselves was high, whereas risk to family and friends, and in their neighborhood was perceived as low. Less than half of women reported reduced access due to fear of contracting Coronavirus, Deprioritization of health services, economic constraints and psychosocial effects were reported due to the imposed lockdown and curfew. Most respondents perceived improvements in quality of care due to short-waiting times, hygiene measures and responsive health personnel. However, this was only reported for the outpatient services. Conclusion. The Government needs to provide food followed by financial support and other basic amenities. This recommendation implies that the Government’s mitigation measures that are focused on public health measures need to include social safety-net approaches for the most vulnerable communities.